Analytical model for the design of piled embankments considering cohesive soils. Issue 4 (17th August 2022) - Pham, T.A.; Wijesuriya, K.; Dias, D.
Abstract : Geosynthetic-reinforced and pile-supported (GRPS) systems have already proven their good performance in supporting embankments constructed over soft soil. The load transfer mechanism in GRPS embankments depends on the complex interaction between the soil in place, the structural elements and the embankment's soil type (cohesive or cohesionless). However, the cohesion influence of the embankment soil has not been well investigated as it is often not considered in the design of such systems. The main aim of this study is to present an analytical model for GRPS embankments that combines several phenomena such as the concentric arches model in cohesive fill soils, the hyperbolic model for the isochrone geogrid curve, and subsoil's consolidation. Three-dimensional numerical analyses are also conducted to evaluate the embankment soil cohesion influence on the soil arching. Both the numerical and analytical results agree that the cohesive embankment fills strengthen the soil arching effect and increase the efficacy if compared with cohesionless embankment fills. A comparison of the analytical model with measured data and other design methods for full-scale field tests proved the proposed model efficiency. The proposed analytical model therefore can be applicable for GRPS embankments with cohesive and non-cohesive fill soils.